Techniques to reduce blood loss during open myomectomy: a qualitative review of literature. (September 2015) - Conforti, Alessandro; Mollo, Antonio; Alviggi, Carlo; Tsimpanakos, Ioannis; Strina, Ida; Magos, Adam; De Placido, Giuseppe
Abstract: Open myomectomy is the most adopted surgical strategy in the conservative treatment of uterine fibroids. According to several studies, the likelihood that a woman could develop uterine myomas is estimated around 75% by the age of 50. Open myomectomy is nonetheless a complicated surgery in terms of blood loss and need for transfusion. Many strategies have been published with the aim of limiting intra and post-operative bleeding complications. The scope of this review is to describe in detail the different techniques reported in literature focusing on their validity and safety.